A Rare Case: Scrotal Hemangioma - Emin Cenan COŞKUN; Muzaffer AKÇAY; Abdullah İLKTAÇ; Fatih GEVHER; Yusuf Özlem İLBEY (Bezmiâlem Science)
Hemangioma is a common soft tissue tumor. Scrotal hemangioma is a very rare benign vascular lesion. There are approximately 55 cases reported so far in the literature. It can cause bleeding, ulceration, pain and aesthetic complaints. Some authors have reported that it may even cause infertility. We presented a case of a 30-year-old male patient who was admitted to the urology clinic with the complaint of a testicular mass which he stated had been present since birth. On physical examination, vascular structures with a mass of approximately 10 cm were observed, filling more than half of the left hemiscrotum. These structures were painless on palpation and externally ecchymotic. On magnetic resonance imaging, as the primary diagnosis, cavernous hemangioma originating from the scrotum wall was considered. Then, the patient underwent excisional surgery under general anesthesia. The pathology result was reported as venous hemangioma. No complications were observed in the follow-ups. After a successful surgical approach, it was observed that the sexual performance of the patient also increased.